(untitled) (International journal of artificial intelligence, 2026)
This article examines the settlement patterns of various tribes that entered Movarounnahr as a result of the Mongol invasion, as well as the socio-political circumstances that emerged through the interaction and assimilation of these tribes with the local population. The study analyzes how these tribes, alongside their gradual sedentarization and integration with the indigenous inhabitants, absorbed the spiritual and cultural values of the highly developed civilization of Movarounnahr and adopted its cultural traditions. Furthermore, the article discusses the transformation of the geographical distribution and nomenclature of these tribes during the Timurid period.